Stimulation of Expressive Language Development in Early Childhood through The Storytelling Method at Al Irsyad Kindergarten Lemahabang - Siti Halimatussya'diyah, Iis; Meliani, Fitri; Suzana, Suzana (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
This research is motivated by the lack of expressive language skills of children in Group B of Al Irsyad Al Islamiyyah Lemahabang Kindergarten. From the initial observations, many children have difficulty expressing their feelings and thoughts. This indicates the need for a fun learning method. The purpose of this study is to improve children's expressive language skills through the storytelling method. By using illustrated storybooks delivered in an interesting way, children are expected to be able to convey their thoughts and feelings. This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which is carried out in two cycles. Each cycle consists of planning, action, observation, and reflection stages. Data were collected through observations of children's activities during the learning process. The results of the study showed a significant increase in expressive language skills. In the pre-cycle, the score was 44.44%. The conclusion of this study is that the storytelling method is effective in stimulating the development of expressive language in early childhood. The increase occurs gradually from the pre-cycle to the second cycle.